The Diagnostic value of serum levels of malondialdehyde (MDA) , superoxide dismutase (SOD) , glutathione peroxidase (GSH-Px) , IL-6, TNF-α, and IL-1β in preserving kidney function in diabetic renal cell carcinoma patients undergoing partial resection: A focus: Diagnostic value of serum levels of malondialdehyde (MDA) , superoxide dismutase (SOD) , glutathione peroxidase (GSH-Px) , IL-6, TNF-α, and IL-1β - Fu, Jia (Journal of Medical Biochemistry, 2025)
Objective:Exploring how dexmedetomidine (DEX) affects renal damage in diabetic patients diagnosed with nephrocellular carcinoma who are receiving partial nephrectomy and Diagnostic value of serum levels of malondialdehyde (MDA) , superoxide dismutase (SOD) , glutathione peroxidase (GSH-Px) , IL-6, TNF-α, and IL-1β. Methods: Randomly selected 100 diabetic patients diagnosed with renal cell carcinoma, all treated at our facility from August 2022 to July 2024, to participate in the study.The patients received either 1.0 μg/kg of DEX or a corresponding volume of normal saline (as the control group) during their partial nephrectomy. Then assessed stress markers before, throughout, and following the surgical procedure to compare the outcomes between the two groups.Inflammatory indicators, TGF-β1/Smad pathway, renal function indicator levels and apoptosis of renal tissue cells. Results: Before administering anesthesia, there were no observable differences in stress levels, inflammatory markers, or TGF-β1/Smad signaling, as well as markers of kidney function between the two groups (P > 0.05). During and after the surgery, the study group exhibited lower serum levels of malondialdehyde (MDA) compared to the control group, while levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were higher (P < 0.05). Also, lower concentrations of IL-6, TNF-α, and IL-1β were recorded in the study group (P < 0.05). Similarly, there were reductions in the expressions of TGF-β1, Smad2 mRNA, and Smad3 mRNA (P < 0.05). Furthermore, the study group showed decreased levels of BUN, Scr, and CysC (P < 0.05). The incidence of renal tissue apoptosis as well as the expression levels of Cleaved Caspase-3 and Ki-67 were significantly reduced in the study group when compared with the control group (P < 0.05). Conclusion; DEX appears to protect against renal function and tissue damage by inhibiting the TGF-β1/Smad pathway and diminishing inflammatory responses.